Exploring 1,3,4-Oxadiazole Derivatives as Potent α-Amylase Inhibitors: Design, Synthesis, and Biological Evaluation - Chavan, Sh.U.; Waghmare, S.A.; Bodke, Sh.S.; Bendale, A.R. (Акад. Е.А. Бөкетов ат. Қарағанды ун-ті КЕАҚ баспасы, 2023)
Diabetes mellitus is a growing global health concern, and α-amylase inhibitors have been recognized as promising therapeutic agents for its treatment. This study aimed to design, synthesize and evaluate 1,3,4- oxadiazole derivatives as potential α-amylase inhibitors. A series of 1,3,4-oxadiazole derivatives were designed and subjected to in silico ADMET, Lipinski's Rule of Five, and drug-likeness analysis. The most promising compounds, SC2 and SC8, were synthesized and their α-amylase inhibitory activity was assessed in vitro. The interactions with the human α-amylase (PDB ID: 6Z8L) which is a target protein, was analyzed through molecular docking studies. The designed compounds complied with Lipinski's Rule of Five and exhibited favourable drug-likeness properties. In silico ADMET analysis predicted good absorption and distribution profiles. SC2 and SC8 demonstrated potent α-amylase inhibitory activity with IC50 values of 36.5±1.5 μg/mL and 45.2±2.1 μg/mL, respectively, compared to acarbose (68.9±3.2 μg/mL). Molecular docking revealed that both compounds formed crucial interactions with key amino acid residues in the enzyme’s active site. The binding affinities of SC2 and SC8 were -10.1 kcal/mol and -9.1 kcal/mol, respectively. The 1,3,4-oxadiazole derivatives, particularly SC2 and SC8, demonstrated potential as α-amylase inhibitors with favorable ADMET properties. These findings provide a basis for further optimization and development of these compounds as novel antidiabetic agents.
Keywords: 1,3,4-oxadiazole derivatives; α-amylase inhibitors; diabetes mellitus; ADMET; molecular docking; Lipinski's Rule of Five; drug-likeness